EVALUASI KEGIATAN SOSIALISASI DAN PELEMBAGAAN ANALISIS SOSIAL EKONOMI DAN GENDER (SAGA) DALAM LITKAJI LINGKUP LITBANG PERTANIAN - NUR SUHAETI, RITA; BASUNO, EDI (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 4, No. 1 Februari 2004, 2012)
Evaluation on SAGA activity in Research and Assessment within the IAARD. Relatively low technology adoption level by end users had triggered application of participatory approach, user oriented technology and more pay attention to user’s social aspects. Socio-economic And Gender Analysis (SAGA) Core Team (SCT) establishment was the initiation of Socialization and Institutionalization program within the Indonesian Agency for Agricultural Research and Development (IAARD). The main objective of the program is to establish SAGA capacity of the researchers and extension workers within the IAARD. The data were gained from eight Assessment Institute for Agricultural Technology (AIAT) by applying structured and semi-structured interviews and Focused Group Discussion (FGD). Respondents for the study were alumnae of the SAGA training workshop. The cascade training workshops were held within the period of 2000 - 2002, beginning from Training of Master Trainers (TOM), Training of Trainers (TOT) and Training of Staff (TOS). Number of the TOM, TOT and TOS were 18; 124; and 416 persons respectively. From the quantity aspect, the number seemed to be promising but not from the quality aspect. The cascade training has not given yet expected result. Each alumna was expected to be SAGA focal points and could establish networking within the region. The main cause was that not all alumnae could disseminate the SAGA approach in each working unit. Less optimal output of the TOM alumnae caused a bumpy regional networking establishment. This reflected that TOM’s alumnae dependency level to the SCT was quite high. It also affected outputs of TOT and TOS. In addition, less understanding on SAGA materials of the respective facilitators in each workshop ended in less understanding of the workshop participants. Various reported results of monitoring and evaluation (Monev) activities showed that the institutionalization of SAGA approach was less optimal and it was reflected by low Monev grade of each observed AIATs.
Keywords: Gender, Social Economics, Socialization, Institutionalization, Research and Development (R& D), Research and Assessment (R& A)